Establishing a tele-clinic service for kidney transplant recipients through a patient-codesigned quality improvement project. Issue 2 (8th April 2019) - Udayaraj, Udaya Prabhakar; Watson, Oliver; Ben-Shlomo, Yoav; Langdon, Maria; Anderson, Karen; Power, Albert; Dudley, Christopher; Evans, David; Burhouse, Anna
Abstract : Kidney transplant patients in our regional centre travel long distances to attend routine hospital follow-up appointments. Patients incur travel costs and productivity losses as well as adverse environmental impacts. A significant proportion of these patients, who may not require physical examination, could potentially be managed through telephone consultations (tele-clinic). We adopted a Quality Improvement approach with iterative Plan–Do–Study–Act (PDSA) cycles to test the introduction of a tele-clinic service. We codesigned the service with patients and developed a prototype delivery model that we then tested over two PDSA improvement ramps containing multiple PDSA cycles to embed the model into routine service delivery. Nineteen tele-clinics were held involving 168 kidney transplant patients (202 tele-consultations). 2.9% of tele-clinic patients did not attend compared with 6.9% for face-to-face appointments. Improving both blood test quality and availability for the tele-clinic was a major focus of activity during the project. Blood test quality for tele-clinics improved from 25% to 90.9%. 97.9% of survey respondents were satisfied overall with their tele-clinic, and 96.9% of the patients would recommend this to other patients. The tele-clinic saved 3527 miles of motorised travel in total. This equates to a saving of 1035 kgCO2 . There were no unplanned admissions within 30 days of the tele-clinic appointment. The service provided an immediate saving of £6060 for commissioners due to reduced tele-clinic tariff negotiated locally (£30 less than face-to-face tariff). The project has shown that tele-clinics for kidney transplant patients are deliverable and well received by patients with a positive environmental impact and modest financial savings. It has the potential to be rolled out to other renal centres if a national tele-clinic tariff can be negotiated, and an integrated, appropriately reimbursed community phlebotomy system can be developed to facilitate remote monitoring of patients.